ERP- SYSTEMS, LOGISTICS AND MECHATRON-ICS SYSTEMS FOR ENSURING THE SMOOTH CONSTRUCTION PROCESS - Bulgakov, Alexey Grigoryevich; Tokmakov, Georgii Evgenyevich (Journal of Applied Engineering Science, 2018)
The article considers possible structures to integrate ERP systems at a building enterprise with low - end information and mechatronic systems – AMS (automated management systems) and MES which handle technological divisions as well as read necessary information. To achieve the information integrity of the construction process a multiagent control system of information and resource flows of industrial divisions together with a mathematical model of the operation is suggested.
Keywords: ERP - system; MES - system; logistic service; TIA technology; intelligent agent; mechatronic systems